Association of paternal HLA-C and maternal killer-cell immunoglobulin-like receptor genotypes in the development of autism - Moriya Gamliel; Karen Anderson; Nurit Yirmiya; Richard Paul Ebstein; David Mankuta (Frontiers Media S.A., 2016)
Natural killer (NK) cells belong to the innate immunity system. Their activity is regulated by inhibitory and activating receptors. The major family of inhibitory receptors is the Killer immunoglobulin-like receptors (KIRs) which recognize MHC class I proteins, mainly HLA-C. The KIR receptor family is further divided into two groups; short tail receptors that are activating and named 2/3DS and long tail receptors that are inhibitory and named 2/3DL. Because immune aberrations have been reported in autistic (ASD) children we decided to compare the KIR: HLA frequencies in ASD children with those of their healthy parents. This study enrolled 49 ASD children from different Israeli families, and their parents. A higher frequency of HLA-C2 allotypes was found among the fathers, while its correspond ligand 2DS1, was found in higher percentage in the maternal group. Nevertheless, a skewed frequency of the combination was not shown in the ASD children. Overall activation analysis pointed to higher activation in maternal than paternal cohorts.